Decreasing incidence of subarachnoid hemorrhage. (12th October 2018) - Nicholson, Patrick; O'Hare, Alan; Power, Sarah; Looby, Seamus; Javadpour, Mohsen; Thornton, John; Brennan, Paul
Abstract : Objective: To determine the incidence and trends in subarachnoid hemorrhage in Ireland using data from a national database. Materials and methods: We performed a retrospective nationwide query of the Irish Hospital In-patient Enquiry System (HIPE). This is a national database of all in-patient activity in acute public hospitals in Ireland. Each HIPE entry records one episode of in-patient care. The study period ranged from 1997 to 2015. Population data was obtained from the Irish Central Statistics Office, and the annual prevalence of smoking from the Irish National Tobacco Control Office. We were therefore able to calculate both crude annual acute subarachnoid hemorrhage (SAH) incidence rates, as well as population-standardized rates, and compared them with trends in the annual smoking rates. Results: The mean number of SAH cases per year is 549, with 465 cases in 1997 and 517 in 2015 (range: 465–624). The absolute incidence of SAH, therefore, remained relatively stable. Due to population increases over time, the population-adjusted rate of SAH therefore decreased, from 126.9/million people/year in 1997 to 111.5/million people/year in 2015. Nationally, there was a decrease in smoking prevalence, from 31% in 1998 to 19.2% in 2015. There was a statistically significant correlation between decreasing smoking rates and decreasing population-adjusted incidence of SAH (P=<0.0001). Conclusions: Our data suggests that the incidence of non-traumatic subarachnoid hemorrhage in our population appears to be decreasing, a decrease which is correlated with decreasing smoking rates. This provides important data both in terms of the epidemiology of SAH, as well as the possible role of public-health interventions in tackling both smoking and declining rates of SAH.